Analisis Kemampuan Aparatur dalam Meningkatkan Kinerja Aparatur di Inspektorat Daerah Kota Bandar Lampung - Yadi Lustiadi (Universitas Bandar Lampung (UBL), 2015)
Intention of this writing is: (1) To know and analyse the ability officer in improvingperformance of officer of Inspectorate of Area of Regency of Bandar Lampung , (2) To know and factors analyst supporting the make up of ability officer in improving performance of officer of Inspectorate of Area of Town Bandar Lampung.Research Method used by descriptive by using analysis qualitative. conducted Descriptive research to depict precisely is nature of and circumstance, symptom or growth symptom in relation of between research with the other symptom society.Result of research indicate that the ability officer in improving officer performance in Inspectorate of Area of Town Bandar Lampung have goodness, that matter is supported with according to between area of duty officer with the education and training which have been followed by the officer. As for factors supporting the make-up of ability officer in supporting officer performance is aspect of job quality, what good relative in executing duty as officer, job amount which still less in certain solution during, and also time accuracy finish the good work relative.